Perlindungan Hak Asasi Manusia (HAM) terhadap Anak sebagai Pelaku Tindak Pidana - Dodik Prihatin A.N (Fakultas Hukum Universitas Islam Jember, 2014)
Human rights possessed by every human being born in the midst of social life. Included in this position a child who also have rights as set in the principles of Human Rights (HAM) both nationally and internationally that the protection of their rights when a child is entangled with legal issues. Relating to the position of children as criminals should also get the protection of his rights before the child is undergoing trial, during and after undergoing trial after undergoing trial as a child in the implementation of the judicial process was still often experienced treatment that should not be accepted by a child. This needs special attention from the government in general and in particular law enforcement officials.